2013
DOI: 10.2174/1875932701306010021
|View full text |Cite
|
Sign up to set email alerts
|

On Thermodynamic Stability of Hydrogenated Graphene Layers, Relevance to the Hydrogen on-board Storage

Abstract: The present analytical study using thermodynamic methods for analysis of data from a number of theoretical and experimental works, devoted to the current problem of thermodynamic stability and related thermodynamic characteristics of the following graphene layers systems: 1) double-side hydrogenated graphene of composition CH -theoretical graphane (Sofo et al. 2007) and experimental graphane (Elias et al. 2009); 2) theoretical single-side hydrogenated graphene of composition CH; 3) theoretical single-side hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 66 publications
(460 reference statements)
0
13
0
Order By: Relevance
“…[53] (1999) in [20]) reported very low hydrogen storage capacity at 303 K, comparable to activated carbon, for graphite nanofibers (GNFs) prepared by catalytic decomposition of ethylene over nickel, iron, copper/nickel and alumina/magnesia catalysts and concluded that they were unlikely storage materials for hydrogen. However, they left the door open by stating that subtle processing effect might convert inactive materials into effective hydrogen sorbents (as has been recently shown in analytical studies [2] [3], and is considered in the present analytical study). As was also noted in [20], the announcement at the MRS meeting did not escape the automakers and Daimler-Chrysler began an evaluation study with the NU group of these "super" hydrogen storage materials.…”
Section: The Northeastern University (Nu) Group [4]-[8] Hydrogen Stormentioning
confidence: 95%
See 4 more Smart Citations
“…[53] (1999) in [20]) reported very low hydrogen storage capacity at 303 K, comparable to activated carbon, for graphite nanofibers (GNFs) prepared by catalytic decomposition of ethylene over nickel, iron, copper/nickel and alumina/magnesia catalysts and concluded that they were unlikely storage materials for hydrogen. However, they left the door open by stating that subtle processing effect might convert inactive materials into effective hydrogen sorbents (as has been recently shown in analytical studies [2] [3], and is considered in the present analytical study). As was also noted in [20], the announcement at the MRS meeting did not escape the automakers and Daimler-Chrysler began an evaluation study with the NU group of these "super" hydrogen storage materials.…”
Section: The Northeastern University (Nu) Group [4]-[8] Hydrogen Stormentioning
confidence: 95%
“…In the present paper are considered, in the light of a constructive critical analysis [2] [3] of a number of data [4]- [12] [20]- [22], some fundamental aspects-open questions, relevant to developing, may be, within several years time frame, of a key breakthrough technology of a compact and energy efficient hydrogen storage in hydrogenated graphite nanofibers (GNFs).…”
Section: Shell Predicts the End Of The Gas Guzzler By 2070 The New Zmentioning
confidence: 99%
See 3 more Smart Citations